Modelování a simulace rizik veřejných investičních projektů - Pavelková, Martina (Vysoké učení technické v Brně. Fakulta stavební)
Výsledky investičních projektů jsou závislé na kvalitě přípravy projektu v předinvestiční fázi a kvalitně provedené realizaci. Kvalitní příprava projektů, jejich hodnocení a výběr vyžadují identifikovat faktory rizika a nejistoty, stanovit dopady těchto faktorů na výsledky projektu a zvažovat opatření na jejich eliminaci nebo snížení. Účelem řízení rizik projektu je tedy v předstihu poznat zdroje možného ohrožení projektu a připravit opatření, která by vedla ke snížení možných dopadů pro projekt na přijatelnou hodnotu. Základním cílem managementu rizika projektů je pak zvýšit pravděpodobnost jejich úspěšnosti a minimalizovat nebezpečí takového jejich neúspěchu, včetně odmítnutí příliš rizikového projektu, který by mohl ohrozit finanční stabilitu investora a vést až k jeho úpadku. Disertační práce je zaměřena na zkoumání různých přístupů k identifikaci rizik a nejistot a jejich následné hodnocení u investičního projektu realizovaného veřejnoprávní korporací, včetně dopadů přípravy projektu na jeho vlastní realizaci a následný provoz. Zároveň budou doporučena možná opatření na snížení rizik tohoto projektu z hlediska jejich nákladů i velikosti snížení rizika. Součástí práce je rovněž rozbor rizik a přínosů projektů připravovaných, realizovaných a ukončených Jihomoravským krajem a návrh registru rizik a registru příležitostí, případně procesu managementu rizik pro Krajský úřad Jihomoravského kraje.

The results of the investment projects are dependent on the quality of project preparation in the pre-investment stage and well-executed implementation. High-quality preparation of the projects, their evaluation and selection of require key risk factors and uncertainties, the impact of these factors on the results of the project and consider measures on their elimination or reduction. The purpose of the risk management of the project is therefore in advance to know the sources of possible threats to the project and to prepare measures that would lead to a reduction in the potential impacts for the project to an acceptable value. The basic aim of project risks management is then increase the likelihood of their success and to minimize the risk of such failure, including their rejection of the venture project too, which could threaten the financial stability of the investor and lead to its decline. The thesis is focused on the examination of the different approaches to identification of risks and uncertainties and their subsequent evaluation on investment project of public corporations, including the impact of the preparation of the project on its own implementation and subsequent operation. At the same time they recommended possible measures to reduce the risk of this project in terms of their costs and the size of the risk reduction. Part of the work is also an analysis of the risks and benefits of the projects planned, realized and terminated by The South Moravian Region and the draft Project Risk Register and the Project Opportunities Register, where appropriate, the risk management process for The Regional Authority of The South Moravian Region.
Modeling and simulation of public investment project risk
Keywords: Analýza rizik; řízení rizik; Moravian Science Centre Brno; Jihomoravský kraj.; Risk analysis; risk management; Moravian Science Centre Brno; The South Moravian Region.